2000
DOI: 10.1557/proc-612-d3.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Integration and Characterization of Low Carbon Content SiOxCyHzLow κ Materials for < 0.18μm[ Dual Damascene Application

Abstract: A CVD-based low κ film was evaluated for inter-metal dielectric in < 0.18 µm generation devices. The film was deposited by conventional rf PECVD method using organosilane compound and oxygen. The measured dielectric constant of the film was 2.7~2.75. The κ value of the film was stable over several weeks and the moisture absorption was minimal. The chemical composition was in the form of SiO x C y H z , where the carbon content was less than 5 atomic %. Blanket film integration study was conducted to find out t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
5
1
Order By: Relevance
“…Contrary to previously published opinion, 5 we have found evidence that humidity plays a very significant role in the electrical conductivity of both irradiated and unirradiated CORAL. Samples stored under vacuum clearly show increased leakage current density with time as the material uptakes moisture.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to previously published opinion, 5 we have found evidence that humidity plays a very significant role in the electrical conductivity of both irradiated and unirradiated CORAL. Samples stored under vacuum clearly show increased leakage current density with time as the material uptakes moisture.…”
Section: Discussioncontrasting
confidence: 99%
“…On the chemical stability side it is suggested that the dielectric constant of such films is stable and moisture absorption is minimal. 5 The generation ͑in terms of device size͒ of microelectronics usually found in military systems, in particular those used in a space environment, is frequently older than the current commercial one, and this is primarily because of the need to develop radiationhardened versions of them. One can therefore conclude that though low-k materials are not used presently in space applications, since they are just being integrated into commercial circuits, they will become of interest for space in the medium term.…”
mentioning
confidence: 99%
“…Different groups have investigated the physicochemical properties of SiOC:H films deposited by radio-frequency ͑rf͒ PECVD. [3][4][5][6][7][8][9][10][11][12] Usually the gas precursor is a mixture of an organosilane ͑e.g., trior tetramethylsilane͒ and an oxidizing agent ͑e.g., oxygen or nitrous oxide͒. The atomic composition appears to be strongly dependent on deposition conditions.…”
mentioning
confidence: 99%
“…The atomic composition appears to be strongly dependent on deposition conditions. A compilation of past works [3][4][5][6][7][8][9][10][11][12] leads to an average film composition of 25% silicon ͑min 9%, max 42%͒, 35% oxygen ͑min 13%, max 61%͒, 20% carbon ͑min 5%, max 26%͒, and 20% hydrogen ͑min 8%, max 46%͒. IR analysis performed by numerous authors indicates the presence of Si-O-Si bonds ͑dominant͒, Si-CH 3 and Si-C-Si bonds ͑usually strong͒, Si-H and C-H bonds ͑whose intensity depends on hydrogen content, but usually small͒.…”
mentioning
confidence: 99%
See 1 more Smart Citation